Optimization of Land Saving and Loss Reducing and Slope Stability Variation Patterns in Open-Pit Mine. (15th April 2021) - Guo, Tongsuo; Zhou, Wei; Li, Zhaolin; Zhang, Chuanwei; Cai, Qingxiang; Tian, Ya; Qin, Huairui; Liu, Fuming; Jiskani, Izhar Mithal; Zhang, Dongxu
Abstract : This study presents different land saving and loss reducing schemes. Comprehensively compare the economic benefits of the schemes. It is shown that the optimal scheme can recover tons of coal resources on the south slope, creating significant economic benefits. Numerical simulation was utilized to analyze the changes of slope stability, deformation, and shear strain increment in the process of land saving and loss reducing. Results found that the slope stability decreases rapidly, and the toe of the slope has to be internally discharged in time to compress the slope. Timely follow-up of in-slope rows can improve slope stability. The position of the slope shear exit changes with the increase of the distance of the inner row, and its stability increases gradually. When the distance of the lower inner row exceeds 120 m, the increase of the internal row distance has little influence on the slope stability. When the inner distance exceeds 60 m in the process of internal dumping of upper platform, the position of potential sliding plane gradually changes from the lower dump to the upper and lower dump with the increase of inner dumping distance. It shows that the stability of the dump will be damaged if the upper dump continues to be discharged. Therefore, the distance between the upper and lower dump sites is more important than 60 m. The stability of the south slope is good in the process of mining and internal drainage, and the overall stability of the south slope is controllable, based on slope radar monitoring.